Problems of women with disabilities in society A qualitative study in Halabja province - عبدالرحیم, د.ئارام ئەسعەد; فايق, سارا عطا; Salahuddin, Hiwa (Sulaimani Journal for Humanities, 2025)
People with disabilities face many problems in all aspects of life from birth, which vary according to the nature of society and the level of culture of individuals. In the Kurdistan Region, these problems are faced by females with disabilities in different proportions. The type of research is descriptive and qualitative. Interview method was used to collect data. Interviews were conducted with 10 female people with disabilities. They were randomly selected. Content analysis was used to analyze the data. As a result, people with disabilities face many problems and obstacles, some of which are natural and others due to social backwardness, lack of awareness of society in general and inexperience in how to deal with social relationships Their personalities and talents, psychologically, stress, anger, sometimes depression and sometimes due to the influence of others suffer from fear and anxiety and lack of self-confidence in society Health and the lack of government assistance funds for the disabled are another of their problems.
Keywords: Problems; Disability; Female; Society